Biomimetic on-a-chip platforms for studying cancer metastasis. (February 2016) - Lee, Esak; Song, H-H Greco; Chen, Christopher S
Highlights: Current angiogenesis-on-a-chip models remain to demonstrate tumor vessel abnormalities. Tumor intravasation models can cover tumor invasion to blood and lymphatic vessels. Organ-on-a-chip models can be combined with angiogenesis models mimicking organotypic metastasis. Abstract : Cancer metastasis is a multi-step, secondary tumor formation that is responsible for the vast majority of deaths in cancer patients. Animal models have served as one of the major tools for studying metastatic diseases. However, these metastasis models inherently lack the ability to decouple many of the key parameters that might contribute to cancer progression, and therefore ultimately limit detailed, mechanistic investigation of metastasis. Recently, organ-on-a-chip model systems have been developed for various tissue types with the potential to recapitulate major components of metastasis. Here, we discuss recent advances in in vitro biomimetic on-a-chip models for cancer metastasis.